Clinical Benefit and Safety of Palbociclib in Hormone Positive Breast Cancer with Visceral Metastasis: Real-World Experience from a Tertiary Cancer Center - Sandeep K. S; Sandhya Appachu; Ravi B. Diwaker; Sai Vivek; Vijai V.S. Simha (Indian Journal of Medical and Paediatric Oncology)
Introduction Palbociclib, the first CDK4/6 inhibitor, has shown promising results in phase III clinical studies by enhancing the efficacy of endocrine therapy (ET) in HR +/HER2– advanced breast cancer. However, real-world data on its use in patients with visceral metastatic disease are limited. We aimed to assess the effectiveness and tolerability of palbociclib in this high-risk population across different lines of treatment.